2007
DOI: 10.1002/arch.20198
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive and blood meal‐induced trypsin genes in Lutzomyia longipalpis

Abstract: Trypsins constitute some of the most abundant midgut digestive proteases expressed by hematophagous insects upon blood feeding. In addition to their role in the digestion of the blood meal, these proteases also have been implicated in the ability of certain pathogens to infect their natural vector. In sand flies, digestive proteases including trypsins were associated with early killing of Leishmania and are believed to play a role in the species-specificity dictating sand fly vectorial capacity. Our group is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…longipalpis, trypsin-like proteins were identified that displaying high sequence similarities to those from P. papatasi. [40][41][42] Also, mutants lacking lipophosphoglycan were more susceptible to digestion by enzymes. 10 Our data consistently showed high parasite mortality at the early stages of L. infantum chagasi infection, which is probably caused by enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…longipalpis, trypsin-like proteins were identified that displaying high sequence similarities to those from P. papatasi. [40][41][42] Also, mutants lacking lipophosphoglycan were more susceptible to digestion by enzymes. 10 Our data consistently showed high parasite mortality at the early stages of L. infantum chagasi infection, which is probably caused by enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Lltryp2, on the other hand, is constitutively expressed as high levels in the non-blood fed female, but is reduced upon blood feeding. At the end of the digestive cycle, Lltryp2 regains its preblood meal levels (Telleria et al 2007). The two trypsin types were identiWed in our EST project (accession numbers EX210491 and EX211460 respectively).…”
Section: Trypsin-likementioning
confidence: 97%
“…In addition to their role in blood meal digestion, these proteases also have been implicated in the ability of certain pathogens to infect their natural vector (Shahabuddin et al 1996). In L. longipalpis, the expression proWles of two trypsin-like genes (Lltryp1 and Lltryp2) were previously characterized (Telleria et al 2007). Lltryp1 expression remains undetected until blood feeding and reaches a peak at 12 h post-blood meal (PBM), returning to pre-blood meal levels at 72 h PBM.…”
Section: Trypsin-likementioning
confidence: 98%
“…longipalpis longevity and this is effect is enhanced if infected flies are stressed [3, 18]. It is known that Leishmania can modulate the digestive enzymes of the sand fly host [1921] and may cause damage to the stomodeal valve in the gut [22]. There is also evidence for an insect immune response towards Leishmania and if the sand fly immune system is appropriately stimulated this can lead to a loss of Leishmania infection [23].…”
Section: Introductionmentioning
confidence: 99%